The first-person pronoun in Mahmoud Darwish’s Divan, Limaza Tarakt al-Hissan Wahidan: Proving “Self” or confrontation with the “Other” - mohammad javad Pourabed; Seyyed Haydar Shirazi; Ahmad Heydari (دراسات فی اللغه العربیه و آدابها)
Words, including pronouns have emotional connotations and implications out of context, and when they are used in a text, their semantic effect is enhanced by the context.  The contemporary poets attempted to use this potential capacity. This means that pronouns, as effective elements, are able to make the text dynamic and stimulate the addressee’s emotions. Like other writers, Mahmoud Darwish has widely used pronouns in order to utilize their potential to convey his emotional experience. He has succeeded to do so because the basic referential and lexical structure of pronouns refers to concepts such as identity, affiliation, power and solidarity. In addition, they are effective components in the time of creating the work and in the context, having a semantic function in line with the poet’s thought. The statistical population of this study includes the first-person pronouns used in the divan by Darwish, Why did you leave the Horse Alone. The authors of this article have examined the dispersion and frequency of this pronoun in the work to explore the implications and the aesthetic values. The method employed is descriptive-analytical. The survey shows that the poet narrates the reality of Palestinians, using the first-person plural pronouns. He describes that reality as a “whirlpool of clashes”. Sometimes, this pronoun is used in the subject position and implies authority and power. Sometimes, it is used in the objective position and connotes a feeble, vulnerable and passive identity. However, the agent in that role is not indifferent and always struggles for a higher position and tries to alter the other’s situation, making him or her passive. Moreover, Darwish tries to promote solidarity in the nation.